2020
DOI: 10.1111/vco.12569
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Felis catus papillomavirus type‐2 DNA and viral gene expression suggest active infection in feline oral squamous cell carcinoma

Abstract: Papillomavirus (PV) infection is associated with development of epithelial cancer in different species, including domestic cat (Felis catus). Felis catus PV type-2 (FcaPV-2) is considered the causative agent of a proportion of feline cutaneous squamous cell carcinoma (SCC), through the transforming properties of its E6 and E7 oncogenes. However, the possible role of FcaPVs in the aetiology of feline oral SCC (FOSCC) is still unclear. The aim of this study was to assess the presence and gene expression of FcaPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 51 publications
(164 reference statements)
3
43
0
Order By: Relevance
“…For instance, HPV-16 E6 induces overexpression of cMyc, which is a transcriptional activator of TERT promoter (9). Recent studies demonstrate that a proportion of FOSCCs is associated with FcaPV-2 infection; importantly, FcaPV-2 biological activity has been previously revealed also in SCCF2 and SCCF3, with this latter cell line harboring higher E6 mRNA amounts (24,26). In this study, expression levels of cMyc, but not TERT, appeared to be correlated with those of E6 in SCCF cells; at first glance, these data suggested that the viral oncogene may up-regulate cMyc as in human counterpart, but this would not contribute to cell transformation through induction of TERT expression in FcaPV-2-related FOSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, HPV-16 E6 induces overexpression of cMyc, which is a transcriptional activator of TERT promoter (9). Recent studies demonstrate that a proportion of FOSCCs is associated with FcaPV-2 infection; importantly, FcaPV-2 biological activity has been previously revealed also in SCCF2 and SCCF3, with this latter cell line harboring higher E6 mRNA amounts (24,26). In this study, expression levels of cMyc, but not TERT, appeared to be correlated with those of E6 in SCCF cells; at first glance, these data suggested that the viral oncogene may up-regulate cMyc as in human counterpart, but this would not contribute to cell transformation through induction of TERT expression in FcaPV-2-related FOSCC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that a sub-group of FOSCC is associated with Felis catus papillomavirus type-2 infection (FcaPV-2), whose oncogenes show transforming abilities comparable to those of HPV-16, thus mimicking HPVrelated hOSCC (22)(23)(24)(25)(26). However, the possible role of FcaPV-2 E6 in the regulation of telomerase and MMPs is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of feline PVs indicate that the same virus can be associated with development of cancers of the skin and mucosal epithelia. Felis catus PV type 2 (FcaPV-2), originally isolated from and then widely associated with pre-neoplastic and neoplastic skin lesions, is detectable in a subset of feline oral squamous cell carcinoma (FOSCC) samples and FOSCC-derived cell lines, where it is transcriptionally active (Lange et al, 2009 ; Altamura et al, 2018a , 2020 ; Munday et al, 2018 ). Accordingly, molecular studies clearly show that FcaPV-2 E6 and E7 oncogenes display biological properties similar to those of mucosal HR HPV-16 in degrading p53 and pRb tumor suppressor proteins (Altamura et al, 2016 , 2018a ).…”
Section: Breaking the Paradigm: Recent Evidence About Animal And Humamentioning
confidence: 99%
“…Accordingly, molecular studies clearly show that FcaPV-2 E6 and E7 oncogenes display biological properties similar to those of mucosal HR HPV-16 in degrading p53 and pRb tumor suppressor proteins (Altamura et al, 2016 , 2018a ). Possible transmission routes between the two anatomical sites have also been hypothesized, such as via skin licking or through the bloodstream carrying viral particles to the epithelium of oral cavity (Altamura et al, 2018b , 2020 ). Of note, other FcaPVs are suspected to infect skin and oral epithelia, such as FcaPV-1, -3, and -4 (Munday and French, 2015 ; Munday et al, 2015 , 2018 ; Mazzei et al, 2018 ; Vascellari et al, 2019 ; Chu et al, 2020 ), however additional experimental data are warranted for any confirmation.…”
Section: Breaking the Paradigm: Recent Evidence About Animal And Humamentioning
confidence: 99%
“…Many studies in human medicine are addressing the association between human papillomavirus infection and HNSCC (39). In cats, accumulating studies are also focusing on molecular biology and the relationship with papillomavirus infection (8,33,40). Studies have also evaluated using cats as animal models for studying emerging targets in human cancer therapy (41).…”
Section: Degree Of Keratinizationmentioning
confidence: 99%